Ukuran Perusahaan, Profitabilitas, Leverage, Likuiditas Dan Pertumbuhan Perusahaan Terhadap Nilai Perusahaan - Nia Dwi Susanti; Eny Kusumawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Company value is investors' perception of a company and is often linked to share prices. In other words, the higher the share price, the higher the company value. Company value is important because it reflects the rate of return on capital for investors. This research aimed to analyze the effectof company size, profitability, leverage, liquidity, and company growth toward company value in non-financial companies on the Indonesia Stock Exchange for the period 2020-2022. The sampling technique used in this research is purposive sampling. A total of 747 companies have met the criteria as observation units. The analytical method used is multiple linear regression analysis. The research results provide empirical evidence that company size and profitability affect the company value. Meanwhile, leverage, liquidity and company growth do nto affect on company value. Keywords: company value, profitability, liquidity, company growth